Sistem Pakar Untuk Mendiagnosa Keluhan Pada Kehamilan Trimester Ketiga - Wati, Embun Fajar; Puspitasari, Anggi (Politeknik Ganesha Medan, 2020)
Limited time in consulting becomes an obstacle for midwives in diagnosing complaints in pregnant women, especially those who are already in the III trimester and approaching the labor process. Misdiagnosis results in inaccuracies in the provision of solutions and actions. Initial treatment that corresponds to the complaints of pregnant women especially the third trimester is expected to reduce mortality rates in the mother and fetus. Expert System can be a timely solution with not too long so as to improve the quality of examination on midwives. The methods used are identification, primary and secondary data collection, forward chaining data analysis combined with bayesian, and evaluation with the calculation of the percentage of system success. Samples taken by 20 patients and 4 patients were declared unsyed because they had only one complaint. Meanwhile, 16 patients had some complaints that complied with the Rules. A total of 11 out of 16 patients or about 70% had valid results between the diagnosis of experts/midwives with the system. It can be concluded that the system works well to diagnose complaints in patients with a third trimester gestational age so that midwives can provide appropriate initial solutions and treatment in reducing maternal and infant mortality.